Soft Capsule Magnetic Millirobots for Region-Specific Drug Delivery in the Central Nervous System - Mair, Lamar O.; Adam, Georges; Chowdhury, Sagar; Davis, Aaron; Arifin, Dian R.; Vassoler, Fair M.; Engelhard, Herbert H.; Li, Jinxing; Tang, Xinyao; Weinberg, Irving N.; Evans, Emily E.; Bulte, Jeff W.M.; et al. (Frontiers in Robotics and AI, 2021)
Small soft robotic systems are being explored for myriad applications in medicine. Specifically, magnetically actuated microrobots capable of remote manipulation hold significant potential for the targeted delivery of therapeutics and biologicals. Much of previous efforts on microrobotics have been dedicated to locomotion in aqueous environments and hard surfaces. However, our human bodies are made of dense biological tissues, requiring researchers to develop new microrobotics that can locomote atop tissue surfaces. Tumbling microrobots are a sub-category of these devices capable of walking on surfaces guided by rotating magnetic fields. Using microrobots to deliver payloads to specific regions of sensitive tissues is a primary goal of medical microrobots. Central nervous system (CNS) tissues are a prime candidate given their delicate structure and highly region-specific function. Here we demonstrate surface walking of soft alginate capsules capable of moving on top of a rat cortex and mouse spinal cord ex vivo, demonstrating multi-location small molecule delivery to up to six different locations on each type of tissue with high spatial specificity. The softness of alginate gel prevents injuries that may arise from friction with CNS tissues during millirobot locomotion. Development of this technology may be useful in clinical and preclinical applications such as drug delivery, neural stimulation, and diagnostic imaging.